Examining Kyai Soleh Darat View of the Concept of Fasting in Tafsr Faiḍ Al-Raḥmān Fī Tarjamāt Tafsīr Kalām Al-Mālik Al-Dayyān - Fikri Ys, Irsyad Al (Hanifiya: Jurnal Studi Agama-Agama, 2022)
This study aims to examine the orientation of the Nusantara interpretation written by Kyai Soleh Darat with a focus on the problem, namely the concept of fasting in Tafsr Faiḍ Al-Raḥmān. Kyai Saleh Darat's tendency towards the field of Sufism, the author observes that the interpretation method used by Kyai Salih Darat tends to be esoteric (isyari') this is what makes the interpretation of fasting according to Kyai Soleh Darat different from some other mufassir's. The data collection technique in this article uses library research techniques with descriptive-analytical methods applied. The results of this article research found that the Kyai's Sufistic interpretation. Salih Darat in the meaning of his isyari, especially in the context of fasting, is very strongly colored by al-Ghazālī's thoughts in the book Iḥyā' 'Ulūm ad-Dn. Kyai Saleh Darat said that the essence of fasting is hunger.